THE RESPONSE OF CORPORATE DIVIDEND POLICY TO THE ABOLITION OF TAX CREDIT IN THE UNITED KINGDOM (U.K.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
By abolishing the tax credit on dividends received by tax-exempt financial institutions in 1997, the effective rate of tax for shareholders such as pension funds increases significantly, and the tax preference for dividends is significantly reduced. The tax-exempt shareholders mainly consist of pension funds and insurance companies with respect to their pension business. This tax-exempt community is the most influential shareholders in many U.K. companies, and their tax preference for dividends may have an important impact on corporate dividend policy. The objective of this study is to examine whether the aggregate dividend payment changes following the 1997 abolition of the tax credit. Using aggregate data in time series from 1974 to 1999, this study finds that the percentage of forecast error in Lintners model does not change significantly between the pre- and post-abolition periods. Hence, there is no evidence that aggregate dividend payment decreases following the abolition of tax credit. This could be interpreted that the aggregate sample of U.K. firms indicates a little intention of changing their dividend policies in response to the abolition of tax credit. This study also investigates whether individual U.K. companies respond to the 1997 abolition of tax-credit. The test results show that the majority of companies in the sample do not change their dividend policies after the abolition of tax credit. It is possible that companies are reluctant to cut their dividend payment since the existing dividend payout could be sustained in the long-run. They also avoid sending negative signals to the market. Thus, companies typically chose to keep a dividend level relatively stable following the tax change in 1997. Only the minority of the U.K. companies experience taxa decline in their dividend payment. This evidence supports the hypothesis that the abolition of tax credit on dividends results in a decrease in aggregate dividend payment in order to satisfy a tax clientele.